Measuring moisture content in a porous insulation material using a hot wire. (January 2015) - Zhang, Tengfei (Tim); Shen, Runlin; Lin, Chao-Hsin; Yin, Jiusheng; Wang, Shugang
Abstract: Porous insulation materials may easily acquire a large amount of moisture when they are exposed to high-humidity conditions. The acquired moisture can cause degradation of insulation performance, micro-organism growth, corrosion, etc. Currently, there is lack of an accurate, simple and inexpensive method for in-situ, nondestructive and rapid measurement of the moisture content in porous materials. This investigation proposes measuring the moisture content by means of the material's volumetric heat capacity using a hot wire. The moisture content is inferred from the change of the volumetric heat capacity before and after the moisture acquirement, which is the ratio of the thermal conductivity to the thermal diffusivity. To evaluate the measurement performance, the method was applied to determine both liquid water and ice content in sponge blocks. The results indicate that the discrepancies in the measured moisture mass content are within ±4% (w/w) between our proposed hot-wire method and the benchmark gravimetric method using a precision balance. Unlike the measurement of the thermal conductivity or the thermal diffusivity, the hot-wire method is insensitive to the contact resistance when measuring the volumetric heat capacity. This method may even be extended to detect foreign substances in porous materials if there is a meaningful difference in the measured volumetric heat capacity before and after the substance intrusion. Graphical abstract: Highlights: A nondestructive method for moisture monitoring in-situ. Both liquid water and ice content accurately determined. Insensitive to contact thermal resistance of this method. May be extended to detect foreign substances in porous materials.